The Effect of Motivation and Job Satisfaction on the Performance of MSME Credit Account Officer Employees at Bank BJB - Muhammad Adhitya Mulyadi; Neneng Hayati (CV. Publikasi Indonesia, 2024)
This research aims to determine the impact of work motivation and job satisfaction partially and simultaneously on the performance of AO Kredit UMKM employees at bank bjb. The research method applied in this study is descriptive verification research. The total research sample was 152 people. This research was carried out in several ways, namely: interviews, questionnaires, observation. Data analysis was used with descriptive analysis, Classical Assumption Test and hypothesis testing which included the t test and f test. The results of the analysis show that the partial influence of work motivation on the performance of AO Credit MSMEs at bank bjb is 32.5%. The partial influence of job satisfaction on the performance of AO Credit MSMEs at bank bjb is 42.8%. The magnitude of the influence of work motivation and job satisfaction on the performance of AO Credit UMKM employees at bank bjb simultaneously is 75.3%.